ReFocus : the films of Pablo Larraín - Hatry, Laura (ReFocus: the international directors series., 2020)
Assessing his work in the context of film aesthetics, philosophy, history, adaptation studies and cultural studies, this is the first book-length English-language anthology about this important director's cinema, offering a wide range of perspectives by a diverse range of international scholars.